OBJEKTIFIKASI DAN MALE GAZE DALAM KUMPULAN CERPEN ZOU NO SHOUMETSU (è±¡ã®æ¶ˆæ»…) KARYA MURAKAMI HARUKI - Wardani, Wilujeng Dwi Kusuma; Suherman , Eman (Japanology: The Journal of Japanese Studies, 2023)
This study examines forms of female objectification and the practice of male gaze in three short stories from the collection titled 象の消滅/Zou No Shoumetsu by Murakami Haruki. Employing a qualitative approach and descriptive method, this research analyzes narrative excerpts from the short stories ねじまき鳥と火曜日の女たち/Nejimaki-dori to kayōbi no onnatachi, ファミリー・アフェア/Famirii afea, and 四月のある晴れた朝に 100 パーセントの女の子に出会うことについて/Shigatsu no aru hareta asa ni 100-paasento no onna no ko ni deau koto ni tsuite/. Data are scrutinized through the perspectives of Martha Nussbaum's objectification theory and Laura Mulvey's male gaze theory. The analysis reveals consistent patterns in female objectification and the practice of male gaze. Women are reduced to mere physical appearances without consideration for individual depth, while male gaze is reflected in the domination of masculine viewpoints focusing on the sexualization of women. Despite differences in context and character interactions among the three short stories, the pattern of female objectification remains consistent. These findings underscore the importance of critical reflection on the representation of women in contemporary Japanese literature and efforts to address gender stereotypes in literary works.